Environmental Effects on the Coefficient of Friction and Tack Adhesion of Formulated Waterborne Coatings - Hall, J.L.; Bevas, C.J.; Hinder, S.J.; Kynaston, E.L.; Lindsay, C.I.; Gruber, P.; Keddie, J.L. (Frontiers in Mechanical Engineering, 2022)
Waterborne coatings emit a low amount of harmful volatile organic compounds (VOCs) into the atmosphere compared to solvent-cast coatings. A typical waterborne formulation for agricultural applications consists of colloidal thermoplastic particles (latex) as the binder, a thickener to raise the viscosity, inorganic filler particles with a water-soluble dispersant, and a colloidal wax to modify surface properties. The formulations typically contain hygroscopic species that are potentially subject to softening by environmental moisture. The hardness, tack adhesion, and coefficient of friction of formulated coatings determines their suitability in applications. However, the relationship of these properties to the components in a coating formulation has not been adequately explored. Furthermore, the relationship between hygroscopic components and properties is an added complication. Here, we have characterized the hardness and tack adhesion of model formulated coatings using a single micro-indentation cycle with a conical indenter under controlled temperatures (above and below the glass transition temperature of a latex binder) and relative humidities. In parallel, we measured the coefficient of kinetic friction, , for the same coatings using a bespoke testing rig under controlled environmental conditions. Across a range of temperatures, RH and compositions, we find an inverse correlation between the coating hardness and . Any correlation of with the roughness of the coatings, which varies with the composition, is less clear. Formulations that contain wax additives have a higher at a low RH of 10%, in comparison to formulations without wax. For the wax formulations, decreases when the RH is raised, whereas in non-wax formulations, increases with increasing RH. Wax-containing coatings are hydrophilic (with a lower water contact angle), however the wax has a lower water permeability. A lubricating layer of water can explain the lower observed in these formulations. The addition of wax is also found to planarize the coating surface, which leads to higher tack adhesion in dry coatings in comparison to coatings without wax. Greater adhesive contact in these coatings can explain their higher friction. Our systematic research will aid the design of seed coating formulations to achieve their optimum properties under a wide range of environmental conditions.